Creating Cleanliness With The Spirit Of Gotong Royong In Muara Betung Village, Ulu Musi Sub-District District Four Lawang - Sandi, Zulia; Arusdi, Arusdi; Suradilaga, Nanda; Dewa , Bara Calang; Rizki , M. Gilang; Effendi , Yanto; Susena, Karona Cahya; Irwanto, Tito (Universitas Dehasen Bengkulu, 2025)
Environmental cleanliness in the community is very important. A clean environment will produce a clean soul, physical and spiritual health for the community. Knowledge about environmental cleanliness can create a clean environment that must be done in groups, namely by mutual cooperation, this can be done routinely, not just stopping when there are activities. Activities carried out in creating cleanliness with a spirit of mutual cooperation and family that have many benefits for the community in Desa Muara Betung Kecamatan Ulu Musi Kabupaten Empat Lawang. Which have a positive impact on maintaining environmental cleanliness. With the spirit of mutual cooperation and togetherness between residents, it can create a family relationship in the community. This mutual cooperation activity has a positive impact on participants and the community, especially in fostering a sense of concern for the environment, creating cleanliness, improving community welfare.